THE CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION OF THE EIGHTH-GRADE STUDENTS OF SMPN 2 UBUD - Luh Putu Darmayani Pulasari; I Komang Budiarta; Anak Agung Putri Maharani (Academic Journal on English Studies (AJOES), 2022)
The present study that used an ex-post facto research with correlation design was intended to figure out the significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMPN 2 Ubud in academic year 2020/2021. The research samples consisted of 38 students who were chosen by means of the cluster sampling method. The data were collected by administering the research instruments in the form of matching cloze procedure tests and short answer task. The obtained data were statistically analyzed by using pre-requisite analysis: normality and homogeneity test and hypothesis testing: Pearson product-moment correlation and t-test. The results of the data analysis clearly revealed the alternative hypothesis was finally accepted. In other words, the research findings have confirmed that there is a significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMPN 2 Ubud in academic year 2020/2021.